Molecular methods in the diagnosis of Clostridium difficile infections: an update. (September 2013) - Le Guern, Rémi; Herwegh, Stéphanie; Courcol, René; Wallet, Frédéric
Nucleic acid amplification techniques (NAATs) represent a major advance in the diagnosis of Clostridium difficile ( C. difficile ) infection. This review analyzes the different options available for a molecular diagnosis of C. difficile infection, as well as the strengths and weaknesses of NAATs. The performances of seven commercials NAATs are compared (BD GeneOhm Cdiff, Illumi gene C. difficile, Xpert C. difficile, BD Max Cdiff, Portrait Toxigenic C. difficile, ProGastro Cd, Seeplex Diarrhea ACE). The sensitivity and the rapidity of NAATs are excellent: additional efforts should focus on the discrimination between infection and colonization. Reporting the DNA load of toxigenic C. difficile in the stool sample may represent a solution. Diagnostic algorithms combining immunoassays and NAATs could also improve the specificity and reduce the global cost of this analysis.